THE RESULTS OF ENRICHMENT OF SAMPLES OF ORE DEPOSITS KAQLMAKIR USING TRADITIONAL AND LOCAL REAGENT “SI” - Salijanova Gulnorakhon Kakharovna; Kutumova Gullola Sabirovna; Nishonov Shokhboz Sherali oglu (Bright Mind Publishing, 2025)
In the Republic of Uzbekistan, at the beneficiation plants, for the enrichment of various ores, traditional reagents manufactured abroad are used. At present, it has become necessary to test local reagents and introduce them into the industry. Replacing traditional reagents with new ones - import-substituting reagents is relevant. Creating reagents made from local raw materials will replace the scarce traditional reagents and save a significant amount of currency.
Keywords: Ore, copper, deposit, material composition, grinding, analysis, valuable component, reagent.